Optimizing customer relationship management through AI for service effectiveness: Systematic literature review - HARTANTO, Aji; VERONICA; PRIHANDOKO, Danang (Applied Computer Science, 2025)
The current technological evolution has resulted in changes in the global business landscape. The technological changes have resulted in an organization's business processes changing due to increased customer expectations that have also changed service standards with customer management tools. The adoption of new technologies, namely artificial intelligence, has become an innovative approach strategy to Customer Relationship Management for organizational sustainability. This article aims to provide literature about integrating AI into CRM using a systematic literature review with bibliometric analysis to explore the latest trends in CRM development influenced by AI technology and the benefits and challenges faced by organizations from AI technology. This study is essential for any industry that adopts AI technology in CRM in organizations. This research was conducted by reading and analyzing 25 articles and papers related to AI and CRM. The 25 studies will be processed using the Vos Viewer tool to visualize the development of CRM trends influenced by AI technology. The study found the benefits of integrating AI-CRM into organizations by increasing operational efficiency and effectiveness, increasing customer interaction, and personalizing services. However, organizations face challenges that require aligning AICRM models with their specific needs, cultural transformation, and balancing the roles and responsibilities of humans and AI within CRM operations. In conclusion, the study found that a thorough understanding of the impact and purpose of the role of AI-CRM is needed, conditioned by the organizational situation, to maximize the benefits and minimize the risks of integrating AI with CRM in an organization.